2017
DOI: 10.1186/s12866-017-1091-6
|View full text |Cite
|
Sign up to set email alerts
|

Growth phase-dependent expression profiles of three vital H-NS family proteins encoded on the chromosome of Pseudomonas putida KT2440 and on the pCAR1 plasmid

Abstract: BackgroundH-NS family proteins are nucleoid-associated proteins that form oligomers on DNA and function as global regulators. They are found in both bacterial chromosomes and plasmids, and were suggested to be candidate effectors of the interaction between them. TurA and TurB are the predominantly expressed H-NS family proteins encoded on the chromosome of Pseudomonas putida KT2440, while Pmr is encoded on the carbazole-degradative incompatibility group P-7 plasmid pCAR1. Previous transcriptome analyses sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Moreover, the effect of an hnsB mutation on the generation time, capsule expression, and bgl expression is stronger at 25 °C compared with 37 and 42 °C [53]. Contrary to the hfp pattern, the expression of sfh and pmr is high during the log phase, although it was observed that the amount of the Sfh protein increases during the stationary phase and Pmr remains relatively constant along the growth curve [55,124,125]. Further research is required to address the different conditions and contexts that might be modulating the expression of the horizontally acquired XS homologs.…”
Section: Xenogeneic Silencer Homologs the Growth Phase And The Envirmentioning
confidence: 97%
“…Moreover, the effect of an hnsB mutation on the generation time, capsule expression, and bgl expression is stronger at 25 °C compared with 37 and 42 °C [53]. Contrary to the hfp pattern, the expression of sfh and pmr is high during the log phase, although it was observed that the amount of the Sfh protein increases during the stationary phase and Pmr remains relatively constant along the growth curve [55,124,125]. Further research is required to address the different conditions and contexts that might be modulating the expression of the horizontally acquired XS homologs.…”
Section: Xenogeneic Silencer Homologs the Growth Phase And The Envirmentioning
confidence: 97%
“…Second, TurA and TurB may compensate for each other functionally during the stationary phase. The number of TurB molecules during the stationary phase was approximately 3,000 molecules per cell, and the number of TurA molecules decreased to 25,000 molecules per cell (Sun et al, 2017). Since the difference in the number of TurA and TurB molecules was smaller during the stationary phase than in the log phase, TurA and TurB may complement each other during the stationary phase if one of them is lost from the cell, resulting in a small number of differentially transcribed genes in KT2440 turA and KT2440 turB.…”
Section: Resultsmentioning
confidence: 93%
“…This difference in the numbers of the differentially transcribed genes after the deletion of turA or turB likely stems from differing numbers of TurA and TurB molecules in the cell. The number of TurA molecules per cell in KT2440 during the log phase was approximately 60,000 molecules, in contrast to the number of TurB molecules per cell, which was less than 1,000 molecules (Sun et al, 2017). On the other hand, during the stationary phase, only 18 and 13 genes were differentially transcribed in KT2440 turA and KT2440 turB, respectively (Figure 1).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations